THE HISTORY OF ARGOTS’ ORIGIN IN ENGLISH SPEAKING COUNTRIES, RUSSIAN AND UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
This article explores the genesis and evolution of argot, a specialized form of language used primarily by criminal and marginalized groups for covert communication. The study traces the origins of argot from the 15th century, starting with its early forms such as rotwelsch in Europe and cant in Britain. It examines the development of criminal slang as it spread through Europe, particularly in Britain and its colonies, including Australia, and later influenced other regions such as Russia and Uzbekistan. The research highlights how argot evolved from a secretive communication tool used by criminals into the broader phenomenon of slang, influencing everyday language. The article emphasizes the relationship between language and society, illustrating how socio-economic and political conditions shape the development of criminal language.